BALKANIZATION AND ORIENTALIZATION? RELATIONAL THEORETHIC APROACH TO UNDERSTANDING GEODIPLOMACY OF EUROPEAN UNION’S ACCESSION PARTNERSHIPS DIPLOMACY - Stefanović-Štambuk, Jelica (National interest, 2024)
This study explores the dynamics of the European Union’s overarching diplomacy of its accession partnership diplomacy within the context of the Western Balkans and the Eastern Partnership. It examines the evolving boundaries and issues spanning inseparable from new exclusions and limits-making by the Union’s geodiplomacy. The focus is on its saddened shift from conducting neighbourhood partnership diplomacy to accession partnership diplomacy with Ukraine, Moldova, and potentially Georgia, and the conduct of accession partnership diplomacy with the Western Balkans over the past two and a half decades This transition has been influenced by the formation of semi-sovereign small states in the Balkans and the strategic encirclement of the region by the EU since 1997. The study also highlights recent developments since mid-2022, particularly the change in the EU’s approach towards Ukraine, Moldova, and potentially Georgia, marking a significant shift from previously denying these states the possibility of accession. This shift reflects Europe’s strategic redirection in response to evolving geopolitical rivalries, particularly with China’s “Global Modernization Order”. The research reveals an increasing complexity in EU accession partnership diplomacy, impacted by regional and global power dynamics. The focus is on contrasts between the EU’s strategies in the Eastern Partnership and the Western Balkans, emphasizing the evolving geodiplomatic context since Russia’s aggression against Ukraine on February 24, 2024. This aggression has dismantled the post-Cold War European order, necessitating a re-evaluation of the EU’s approach to its neighbouring countries. The study addresses the surprising disparities in the Union’s diplomatic engagements between the Eastern European Partnership and the Western Balkans. Despite seeming continuity, recent events challenge existing theoretical frameworks and empirical findings, requiring more profound analysis. The unexpected evolution from neighbourhood partnership diplomacy to accession partnership diplomacy with Ukraine, Moldova, and potentially Georgia calls for rethinking Europe’s geostrategic stance and implications for the EU’s enlargement policy. Findings indicate that the EU’s accession partnership diplomacy has shifted significantly due to evolving geodiplomatic realities of rivalry. The aggression of Russia against Ukraine has disrupted the previous order, leading the Union to reconsider its approach towards Eastern European neighbours. This research underscores the influence of global rivalries, particularly with China, on the EU’s diplomatic strategies. The evolving geopolitical tensions have necessitated a more nuanced approach to accession partnership diplomacy, incorporating broader global strategic considerations. Challenges related to the EU’s approach to semi-sovereign states and the balancing act required to manage internal and external relations are identified. The study suggests that the EU’s geodiplomatic strategies need to adapt to the changing global order, addressing pressures from both Western and non-Western powers. It advocates for a more flexible and adaptive approach in EU accession partnership diplomacy, highlighting the need for continued engagement with Eastern European countries and the Western Balkans while navigating the broader geopolitical landscape. In conclusion, the study argues that the EU’s accession partnership diplomacy must evolve in response to a dramatic disruption of human entanglements with nature demanding mutuality as the only relation securing the continuation of human existence on this planet. A geodiplomatic realignment is necessary to address these new realities, ensuring that the EU remains a pivotal player by reinvigorating the European integration process and shaping the future of global diplomacy.